The influence of forest management systems on the environmental impacts for Douglas-fir production in France - González-García, Sara (2018)
The environmental wood profile, all over its life cycle, is a subject of interest for industries within the forest sector. Douglas-fir is a wood species with multiple applications and high productivity. In Europe, France is the country with the largest area dedicated to the cultivation of this tree species.This study aims to quantify the Douglas-fir forestry environmental impacts under different management practices performed in France. This study presents detailed life cycle inventories of both intensive and extensive scenarios, including all the processes from site preparation to logging activities.The results showed that stand establishment operations, tending and logging were the main stages responsible for the environmental impacts in both scenarios. The requirement of numerous thinning steps prior to the final cutting, which require machines with large fuel consumption, also had a negative influence. The logging stage, which includes the final cutting and the corresponding forwarding and loading onto trucks, also accounted for a significant contribution to all the categories. When the environmental results were compared with other life cycle studies on pine, eucalyptus and spruce, similar trends were identified in spite of the different management practices (low or high intensive scenarios), system boundaries and forest systems intensity (frequency of activities) considered.